Investigating Relationship Between Economic Value Added, Market Value Added And Shareholder's Wealth Creation - Panigrahi, Shrikant; Yuserrie, Zainuddin; Noor Azlinna, Azizan (2014)
Profit maximization and increasing shareholder’s wealth have been one of the most crucial concepts for the organization. The corporate manager and shareholders rely upon the traditional accounting measures like net income, Earnings per share (EPS), Return on Equity (ROE), Return on Net worth (RONW), Return on Capital Employed (ROCE) to measure the value created by the firm. But this study utilizes economic measures like Economic Value Added (EVA) and Market Value Added (MVA) combined with the accounting measures to perform a comparative study in order to conclude the most appropriate measures for the creation of shareholder’s wealth. The EVA of 28 construction companies from the total 43 construction companies listed in Bursa Malaysia were selected for the study and analyzed during the period of 2003 to 2012. Overall the result for the study found that very few of the construction companies were having positive EVA for the creation of Shareholder’s wealth. It was also found that there is a strong relationship between created shareholder’s value and economic value added. Thus it is very important to know that whether in the long run the shareholders wealth would be maximized through the usage of EVA as a performance measurement tool. Furthermore, depending on the statement of EVA concept rather than accounting measures would help the shareholder’s for future investment decisions and managing their investment portfolios.